Turas Ulama Nusantara: Al-Akhlaq Lilbanat Karya Syekh Umar Baradja dan Aktualisasinya dalam Pendidikan Islam Indonesia - Aghita Wahyuningsih; Yusuf Hanafiah (Bulletin of Indonesian Islamic Studies, 2022)
The book of Al-Akhlaq Lilbanat by Sheikh Umar ibn Ahmad Baradja can be used as an intermediary in overcoming the current moral condition. The purpose of this article was to find out the moral education values in the book Al-Akhlaq Lilbanat. This paper was a study of Sheikh Umar ibn Ahmad Baradja's views regarding women's moral education, using a library research model with data sources from the book Al-Akhlaq Lilbanat. The data collection techniques used are content analysis and deduction methods by concluding data sources and then analyzing them in detail. The results of the study indicate that the values ​​of moral education in the books of Al-Akhlaq Lilbanat volumes I and II are interrelated, such as morality towards Allah SWT, Prophet Muhammad saw, family, relatives, servants, neighbors, teachers, and friends. Volume III contains some women's etiquette in doing things. The values ​​of moral education in the book Al-Akhlaq Lilbanat are in line with Islamic education as well as actual conditions for women in the contemporary era of Indonesia. This book can be used as a guide that was practical and easy to understand and can be a solution to handling problems that occur in the contemporary era.